The Case for a Digital World Heritage Label. (Information & Culture, 2022)
Much of humanity's most important digital heritage is under corporate control, which poses several threats to its longevity and authenticity. However, public institutions have little authority to intervene and preserve it, and their doing so is not always a desirable alternative. The goal of this article is to propose a mitigation of this dilemma. I do so in three steps. First, I introduce the concept of digital world heritage , which denotes digital artifacts with a value beyond their utility to any single individual or community. Second, I specify three ways commercial management threatens digital world heritage. Third, I argue that many of these threats may be mitigated by the introduction of a digital world heritage label. This proposal, I contend, does not interfere with the integrity of private data controllers since it does not involve the donation of data archives, yet it does support the long-term preservation of digital heritage.